(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Nowadays many different approaches to higher education are discussed in the light of the requirements of the Ministry of education and science and other educational authorities. The importance and necessity of satisfying the needs of population in education, providing with accessibility of a qualitative education and integration of education and scientific-technical achievements are usually emphasized.